Covid‐19 pandemic and consumer‐employee‐organization wellbeing: A dynamic capability theory approach. Issue 1 (20th July 2021) - Nayal, Preeti; Pandey, Neeraj; Paul, Justin
Abstract: The consumers, employees, and organizations have been deeply impacted by Covid‐19 pandemic. The present study offers a detailed coping mechanism for organizations based on the extant literature and content analysis of responses of senior management executives. The study is based on semi‐structured long interviews with senior executives from various industries. Various measures have been identified for firms as a coping strategy for crisis management and customer well‐being. Covid‐19 has changed the way individuals live. This study suggests that firms should come forward for well‐being of their employees in this new normal. One of the major shifts due to pandemic is in consumer behavior and their consumption habits. Pandemic made consumers go for digitization, think for hygiene, sustainability, and local products. And firms should keep the changed consumer behavior in mind while manufacturing the products. Furthermore, present study suggests that firms can create a positive image of their company by doing CSR activities for society's well‐being.